Coping strategies and mental health: A web-based survey among the Italian population dealing with COVID-19 - Chiara Rossi; Francesca De Salve; Martina Agliati; Osmano Oasi (Research in Psychotherapy, 2022)
Coronavirus disease (COVID-19) continues to be a highly stressful event with a major impact on psychological mental health worldwide. The use of different coping strategies may change the perception of psychological well-being during the pandemic. The present study aims to explore psychological mental health in relation to sociodemographic variables and to analyze the coping strategies of the Italian population in dealing with COVID-19. Implications for clinical interventions are reported. A total of 537 individuals (>18) participated in the survey completing measures of sociodemographic data, general psychological well-being, and coping strategies. Results found that females, students, and unmarried people reported the lowest levels of well-being. Specifically, the coping strategy called positive attitude was positively correlated with psychological well-being, whereas avoidance and social support strategies negatively influenced well-being. Understanding beneficial coping strategies is central to optimally manage the long-lasting of the current COVID-19 situation and may be useful for mental health professionals in treating patients suffering psychologically from the pandemic.